Biological modification of seawater chemistry by an ecosystem engineer, the California mussel, Mytilus californianus. (25th July 2019) - Ninokawa, Aaron; Takeshita, Yuichiro; Jellison, Brittany M.; Jurgens, Laura J.; Gaylord, Brian
Abstract: Marine habitat‐forming species often play critical roles on rocky shores by ameliorating stressful conditions for associated organisms. Such ecosystem engineers provide structure and shelter, for example, by creating refuges from thermal and desiccation stresses at low tide. Less explored is the potential for habitat formers to alter interstitial seawater chemistry during their submergence. Here, we quantify the capacity for dense assemblages of the California mussel, Mytilus californianus, to change seawater chemistry (dissolved O2, pH, and total alkalinity) within the interiors of mussel beds at high tide via respiration and calcification. We established a living mussel bed within a laboratory flow tank and measured vertical pH and oxygen gradients within and above the mussel bed over a range of water velocities. We documented decreases of up to 0.1 pH and 25 μ mol O2 kg −1 internal to the bed, along with declines of 100 μ mol kg −1 in alkalinity, when external flows were < 0.05 m s −1 . Although California mussels often live in habitats subjected to much faster velocities, sizeable populations also inhabit bays and estuaries where such moderate flow speeds can occur > 95% of the time. Reductions in pH and O2 inside mussel beds may negatively impact resident organisms and exacerbate parallel human‐induced perturbations to ocean chemistry while potentially selecting for improved tolerance to altered chemistry conditions.